The possibilities of hair analysis in the determination of involuntary doping in sports - Midio, A. F.; de Moraes Moreau, R. L.; Silva, O. A. (Sports Medicine, 2001)
Although not yet fully recognised by international sporting committees, hair analysis in doping control may be a useful adjunct to drug testing of urine. It may permit access to retrospective information and the identification of banned substances, especially when exogenous abuse has to be distinguished from other forms of involuntary exposure to identical substances. Negative hair results coupled with positive urine samples may be used to draw conclusions of involuntary doping in sports whenever athletes claim not to have ingested any drug, identical substances are present in their environment or are normal constituents of food and beverages served to them immediately before the competition. Two cases are well described in the literature in which hair analyses were fundamental in documenting positive doping after urinalysis. In Brazil, 2 cases of athletes testing positive for banned substances caught our attention because of the possibility of involuntary doping; hair analysis, if performed, may have helped to clarify the results of the urinalysis. Despite the fact that it cannot be used for routine control and overrule positive urinalysis, hair analysis can detect long term exposure as well as those substances which are not excreted in urine. In the current International Olympic Committee (IOC) code, hair analysis is not yet considered useful even in special cases of doping control.